An Analysis of Flasback Plot in the Inception Movie - Puspitasari, Ni Putu Riana (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This study is entitled “An Analysis of flashback plot in the Inception Movie.” Movie Inception by Christopher Nolan as the objects of the research. The aims of this study were (1) to describe the plot arrangement of the Inception movie and (2) to describe the type of the plot in the Inception movie. This study used the theory proposed by Holman (1980) to conduct this study. Descriptive and qualitative method were used in this study, in order to collect the data. Such as downloading the movie from the internet, watching and listening to the movie throughly, classifying various fragments of sentences, dialogues, and scenes. Then, examine, analyze, and interpret these fragments in order to understand the plot structure according to the theory. The results reveal that the plot structure of "Inception" includes three main parts: the beginning, middle, and end. The middle part stands out due to its complex problems, which make the story more engaging while still entertaining. Moreover, "Inception" is characterized as a flashback plot structure, with key elements including exposition, rising action, climax, falling action, and catastrophe.